رأي ابن خلدون في تأسيس الدولة وآثارها في الدول الإسلامية المعاصرة - Lanang Hutama Yurivda Hardian Mada; Moh. Mujibur Rohman (Universitas Darussalam Gontor, 2024)
This article explores the contributions of Ibn Khaldun, a prominent Islamic scholar and the author of